2019
DOI: 10.1111/mpp.12896
|View full text |Cite
|
Sign up to set email alerts
|

Research advances in the Pyrenophora teres–barley interaction

Abstract: Summary Pyrenophora teres f. teres and P. teres f. maculata are significant pathogens that cause net blotch of barley. An increased number of loci involved in P. teres resistance or susceptibility responses of barley as well as interacting P. teres virulence effector loci have recently been identified through biparental and association mapping studies of both the pathogen and host. Characterization of the resistance/susceptibility loci in the host and the interacting effector loci in the pathogen will provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(84 citation statements)
references
References 147 publications
(294 reference statements)
1
83
0
Order By: Relevance
“…In our study, we have observed that the Pyrenophora strain was capable of promoting the growth of the plant and its cold tolerance. This would be the first time that a benefit of the Pyrenophora-plant interaction has been described, this genus is best known for pathogens, such as Pyrenophora teres, causal agent of net blotch of barley 41 . The beneficial role observed in B. oleracea by Pyrenophora could be due to the defensive capacity of cruciferous plants through secondary metabolites such as glucosinolates, not present in other plant groups, which is why a possible pathogen in a species may be a harmless symbiont in Brassica.…”
Section: B Oleracea Accession Mbg-brs0426 Mbg-brs0106 Mbg-brs0292 Mbmentioning
confidence: 98%
“…In our study, we have observed that the Pyrenophora strain was capable of promoting the growth of the plant and its cold tolerance. This would be the first time that a benefit of the Pyrenophora-plant interaction has been described, this genus is best known for pathogens, such as Pyrenophora teres, causal agent of net blotch of barley 41 . The beneficial role observed in B. oleracea by Pyrenophora could be due to the defensive capacity of cruciferous plants through secondary metabolites such as glucosinolates, not present in other plant groups, which is why a possible pathogen in a species may be a harmless symbiont in Brassica.…”
Section: B Oleracea Accession Mbg-brs0426 Mbg-brs0106 Mbg-brs0292 Mbmentioning
confidence: 98%
“…Geschele (1928) has first demonstrated the resistance to P. teres f. teres to be quantitatively inherited ( Clare et al, 2020 ). The genetic control of resistance to P. teres in barley was first conducted in United States in 1955 ( Afanasenko et al, 2007 ).…”
Section: Net Blotch Disease Managementmentioning
confidence: 99%
“…From 1973 to 2011, other reviews have been published describing the disease epidemiology and the host resistance toward Ptm ( Mclean et al, 2009 ; Liu et al, 2011 ). In 2020, Clare and collaborators reported the brief consensus maps for all loci published for both barley and P. teres ( Clare et al, 2020 ). To the best of our knowledge, no review has yet described the pathology of the fungus in relation with biological means to increase the resistance of the host.…”
Section: Introductionmentioning
confidence: 99%
“…Ptt, by contrast, has a lengthy association with barley that may go beyond the earliest written records of leaf diseases. Ptt produces both necrotrophic effectors, characteristic of pure necrotrophs, and avirulence genes, characteristic of biotrophs, and is notable for complex host-pathogen genetic interactions [12,41,42] compared to Ptr, where three main effectors explain most of the disease [43], and Ptm where minor effect QTL condition disease [44]. In general, the phylogeny presented supports the diversification of Ptt and recent divergence of Ptm and Ptr [11,30].…”
Section: Pyrenophora Whole Genome Comparative Analysismentioning
confidence: 60%